Analisa Penerapan Proyek Rempang Eco City Yang Mengabaikan Hak Ulayat Dan Melukai Keadilan Masyarakat Adat - Ramadhan, Dany; Dhayinta Septya Martha; Nurul Laili Fadhilah S.H., M.H; Warah Atika S.H., M.H (Universitas Kapuas, 2024)
The analysis of land ownership conflicts on Pulau Rempang within the framework of UUPA, the constitution, and Utilitarianism's theory of justice, as well as understanding the reasons for selecting Pulau Rempang as the location for the Rempang Eco City project, is of a normative or doctrinal nature. It examines legal regulations, the constitution, and theories of justice in the context of land conflicts on Pulau Rempang. The importance of protecting the customary rights of indigenous communities in the context of national strategic development is crucial. The Basic Agrarian Law (UUPA) should be applied while considering the rights of indigenous communities, as recognized in the constitution. The conflict on Pulau Rempang reflects disagreement between indigenous communities and the government regarding relocation for Rempang Eco City. Resolving land ownership conflicts on Pulau Rempang requires an approach that considers customary rights, consistency with the constitution, and Utilitarian principles of justice. The government must acknowledge the presence of indigenous communities in the context of national strategic development. The choice of Pulau Rempang as the location for the Rempang Eco City project should consider social and environmental impacts, as well as the involvement of local communities in the development process.